Biogas Production from Various Vegetable Waste Using the Mesophilic Batch Process - Chusna, Firda Mahira Alfiata; Auliyasari , Annita; Nakita , Feren; Hanum, Farrah Fadhilah; Amelia , Nadiatika (Journal of Applied Agricultural Science and Technology, 2024)
Vegetable waste is a significant component of both household and food industry waste. If not properly managed, the accumulation of this waste can harm the environment, primarily due to the unpleasant odor it generates. One effective way to utilize vegetable waste is through anaerobic digestion process. This method not only enhances the quality of waste but also has the added benefit of producing biogas, a form of renewable energy. Therefore, this research aimed to examine the potential of vegetable waste in producing biogas. Anaerobic digestion process was performed on three different types of vegetables, namely cabbage, kale, and long beans, with co-digestion as cow dung. This process was performed in mesophilic batch anaerobic reactor with a fermentation time of 30 days. The highest biogas yield for 30 days was obtained from long bean waste, 1853.76 ml biogas/g COD. Observations were made on waste at the beginning and end of the process to determine the value of removing chemical oxygen demand (COD). Reducing COD value was necessary to examine whether the quality of waste has improved and ready to be used in the environment. The results showed that long beans have the lowest COD removal efficiency value, 31.54%. Due to the high lignin content in these vegetables, there is a need for further research regarding the pretreatment of vegetable waste before anaerobic decomposition process begins. Meanwhile, the highest COD removal efficiency was achieved by kale vegetable waste at 45.35%.